Making Women's Voices Count : Addressing Gender Issues in Disaster Risk Management in East Asia and the Pacific - World Bank (World Bank, Washington, DC, 2017)
This note on making women's voices count addressing gender issues in disaster risk management (DRM) in East Asia and the Pacific (EAP) is the first in a series of guidance notes targeting World Bank staff, clients and development partners. The note gives an overview of the links between gender and disaster risk management, identifies the key operational bottlenecks, and recommends strategies and resources. Grounded in extensive field work in Lao PDR and Vietnam, and drawing on the significant amount of material already available, these guidance notes are intended to be first stop, practical documents that can be used to design and implement gender dimensions into disaster risk management work across the EAP region. The target audience is World Bank staff, clients and development partners active in the fields of gender and DRM. A gender sensitive DRM approach takes both women's and men's different needs, constraints and opportunities into account throughout the whole project cycle, thereby strengthening community disaster resilience and making DRM interventions more effective. Addressing gender issues contributes to reducing women's vulnerabilities and increases their resilience to overcome the impacts of disasters. When done well, women and men can both benefit, and women can be empowered to make decisions and contribute to household recovery.